2017
DOI: 10.1111/petr.13039
|View full text |Cite
|
Sign up to set email alerts
|

Fatal graft‐versus‐host disease after living‐donor liver transplantation from an HLA‐DR‐mismatched donor

Abstract: Acute GVHD is a rare complication after liver transplantation that has a high mortality rate. We experienced an infant case complicated with acute GVHD. An 8-month-old infant with biliary atresia underwent LDLT with a graft obtained from his mother. Their HLAs showed a donor-dominant one-way match, not at HLA-DR but at HLA-A, HLA-B, and HLA-C (recipient; A 31/33, B 51/54, C 1/14, DR 9/11, donor; A 31/-, B 51/-, C 14/-, DR 8/11). The patient exhibited a high fever, skin rash, and diarrhea, and was diagnosed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 21 publications
(25 reference statements)
2
14
0
Order By: Relevance
“…There have been three case reports describing development of GVHD with donor-dominant one-way HLA matching at only two loci of HLA-A, -B, and -DR, although in two of these reports, analysis was only at the antigen level. [7][8][9] Some similar cases of transfusion-associated GVHD have also been reported; 15 however, in our study, none of 41 such cases in groups 2-5 developed GVHD. In these cases, GVHD did not develop, even in those with donor-dominant one-way HLA matching at all three loci of HLA-C, -DQ, and -DP.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…There have been three case reports describing development of GVHD with donor-dominant one-way HLA matching at only two loci of HLA-A, -B, and -DR, although in two of these reports, analysis was only at the antigen level. [7][8][9] Some similar cases of transfusion-associated GVHD have also been reported; 15 however, in our study, none of 41 such cases in groups 2-5 developed GVHD. In these cases, GVHD did not develop, even in those with donor-dominant one-way HLA matching at all three loci of HLA-C, -DQ, and -DP.…”
Section: Discussionsupporting
confidence: 68%
“…Moreover, GVHD did not develop where all HLA loci were donor-dominant one-way HLA matched or identical combinations, although this level of HLA compatibility can theoretically lead to GVHD. Shimata et al reported a case of GVHD with donor-dominant one-way HLA matching at the three major histocompatibility complex class 1 loci, HLA-A, -B, and -C. 9 Two cases were similarly matched in our study; however, neither developed GVHD. Additionally, we surmise that HLA matching status at HLA-C, -DQ, and -DP might have limited significance for the occurrence of GVHD.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Reportedly, a number of risk factors for GVHD after LTx have been described, including HLA matching, recipient age older than 65 years, transfer of graft lymphocytes, African American race, multiorgan transplant, HCC, retransplant due to preexisting immunosuppression, immunosuppression before transplant, and large age difference between donor and recipient . However, because it is so rare, preventive treatment for GVHD after LTx is not commonly applied.…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of GVHD post SBTx or MVTx ranges between 9% and 29% but much rare post-isolated LTx with an estimated incidence of 0.1%-2% in adults and a mortality rate as high as 85%. [2][3][4][5][6][7][8][9] In pediatric, the occurrence of GVHD-post-isolated LTx is even rarer and only few cases have been reported world while [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] ; however, under reporting may contribute to the rarity of the condition due to nonspecific nature of the presenting symptoms and the associated high mortality.…”
Section: Introductionmentioning
confidence: 99%